Characterization of conformational and oligomeric states of proteins - Ahmad Fuad, Fazia Adyani (Springer Nature Singapore, 2018)
Oligomerization and conformational changes of proteins in solutions are advantageous for their structural and functional control. The advancement in biophysical characterization analyses, such as Size Exclusion Chromatography coupled with Multi-Angle Light Scattering (SEC-MALS) has shed lights in understanding the underlying mechanisms of actions for protein molecules. This chapter focuses on three types of protein analysis; SEC-MALS, native PAGE and continuous enzymatic assays of the bacterially expressed cofactor-independent phosphoglycerate mutase from Leishmania mexicana (Lm-iPGAM), which was shown to exist in different oligomeric and conformational states in solution. The outcome of this analyses has paved the way towards understanding the behavior of Lm-iPGAM in solution, which is important for further structural and functional studies.